FORMATION OF SOCIAL RELATIONS IN ANCIENT SOCIETIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the historical forms of social assistance in ancient societies, its religious, cultural and social foundations. The principles of humanism in ancient civilizations are revealed on the example of support within the tribe and family, support based on religious beliefs, social services provided by the state and charitable activities. Also, social assistance mechanisms such as zakat, sadaqakh, vaqf within the framework of Islam are widely covered. The article also deals with the social reforms being carried out in Uzbekistan today, the development of the social assistance system, issues of tolerance and tolerance. The relevance of forming the qualities of tolerance, tolerance and humanity in social work specialists is emphasized.